2018
DOI: 10.1103/physrevlett.121.060502
|View full text |Cite
|
Sign up to set email alerts
|

Fast and Unconditional All-Microwave Reset of a Superconducting Qubit

Abstract: Active qubit reset is a key operation in many quantum algorithms, and particularly in quantum error correction. Here, we experimentally demonstrate a reset scheme for a three-level transmon artificial atom coupled to a large bandwidth resonator. The reset protocol uses a microwave-induced interaction between the |f,0⟩ and |g,1⟩ states of the coupled transmon-resonator system, with |g⟩ and |f⟩ denoting the ground and second excited states of the transmon, and |0⟩ and |1⟩ the photon Fock states of the resonator.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
134
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 150 publications
(144 citation statements)
references
References 45 publications
3
134
0
Order By: Relevance
“…Figure 5(a) shows the population dynamics. As expected, the population in 2 Y ñ | decays rapidly under the constant guess fields, while 3 Y ñ | exhibits only slow decay and the population in 1 Y ñ | is almost conserved. The respective decay rates and control fields are shown in figures 5(b) and (c).…”
Section: Optimization With An Extended Set Of Control Fieldssupporting
confidence: 79%
“…Figure 5(a) shows the population dynamics. As expected, the population in 2 Y ñ | decays rapidly under the constant guess fields, while 3 Y ñ | exhibits only slow decay and the population in 1 Y ñ | is almost conserved. The respective decay rates and control fields are shown in figures 5(b) and (c).…”
Section: Optimization With An Extended Set Of Control Fieldssupporting
confidence: 79%
“…Here we demonstrate a superadiabatic protocol in the microwave regime using circuit quantum electrodynamics as the experimental platform (26). This is an important task in quantum control, where efficient and fast state preparation is needed as an initial step for many algorithms (27,28). Our experiment employs a superconducting transmon circuit (29), where the first three states are addressed by microwave fields with the goal of populating the second excited state, while starting from the ground state and without populating the first excited state.…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that the system can be steered by multi-tone microwave drives into a steady-state that leaves the qubit in the ground state [21]. Recently, in a paper also including a review of other reset methods, a fast unconditional reset protocol was demonstrated in an architecture using two low quality factor resonators, one for qubit readout and one for qubit reset [22].…”
Section: Introductionmentioning
confidence: 99%